Diversity of Fish Fauna at Peraran and Punan Bah, Batang Rajang, Kapit, Sarawak - Goh, Hao Chin (Universiti Malaysia Sarawak (UNIMAS), 2015)
A study was carried out to document the fish composition and diversity as well as selected water quality parameters at Peraran and Punan Bah, Batang Rajang, Kapit due to the lack of published information on these two areas. Eight stations were selected from downstream area (Peraran) and nine stations from upstream area (Punan Bah). Fish sampling gears such as monofilament gill nets of different mesh sizes, three-layered nets, cast net, electroshocker device and scoop nets were used. A total of 916 fish individuals were caught from all stations with Cyprinidae as the dominant family (75.8 %), followed by the family Balitoridae (8.2 %), Siluridae (7.9 %), Bagridae (3.3 %), Pangasiidae (2.1 %), Channidae (1.0 %), Pristolepididae (0.8 %), Zenarchopteridae (0.6 %), Cobitidae (0.2 %), Mastacembelidae (0.1 %), Osphronemidae (0.1 %) and Sisoridae (0.1 %). The dominant species recorded was Rasbora rutteni with 140 individuals, followed by Cyclocheilichthys apogon with 94 individuals and Rasbora lateristriata with 89 individuals. The downstream area of Peraran, Batang Rajang has higher species composition and diversity (1.77) compared to the upstream area (1.66).